Does the Soil Tillage Affect the Quality of the Peanut Picker? - Lopes de Brito Filho, Armando [UNESP]; Morlin Carneiro, Franciele; Costa Souza, Jarlyson Brunno [UNESP]; Luns Hatun de Almeida, Samira [UNESP]; Patias Lena, Bruno; Pereira da Silva, Rouverson [UNESP] (MDPI, 2023)
Machine harvesting is an essential step of crop production, considering a dynamic operation, and is subject to losses due to several factors that affect its quality. The objective of this study was to evaluate the quality of mechanized peanut pickers in the three soil tillage operations using Statistical Quality Control (SQC) tools. We conducted the experiments in a peanut field located at 21°20′23″ S and 47°54′06″ W of Brazilian peanut farmers. We used Statistic Control Quality (SQC) experimental design to monitor peanut losses during machine harvesting. The treatments evaluated were three soil tillage operations: conventional (CT), rotary tillers (RT), and hoe (RH). The quality indicators were collected inside the picker’s bulk tank. Statistical analyses used were descriptive statistics and SQC tools (run charts, control charts, and the Ishikawa diagram). The process was considered stable for indicators: whole pods (CT, RT, and RH), broken pods (CT, RT, and RH), and hatched pods (CT, RT, and RH), while the other indicators showed points that were out of control. With the application of SQC tools, it was possible to identify the factors that caused the increase of variability in peanut harvesting, listing the points to be improved to support decision-making, always aiming to increase this operation’s quality.
Keywords: Arachis hypogaeaL; harvesting mechanization; impurity; qualitative losses; statistical process control